'Building future politics': projectivity and prefigurative politics in a Swedish social center. (3rd September 2021) - Creasap, Kimberly
ABSTRACT: This article contributes to the concept of prefigurative politics by sharpening the conceptual distinction between future-oriented prefiguration and projectivity. My research suggests that a social movement group's orientation to the future is an important dynamic in how prefigurative action unfolds. Based on a case study of the Swedish autonomous collective Kulturkampanjen and the social center they built, Cyklopen, I analyze three dimensions of projectivity: reach (temporal extension into the short- or long-term future), contingency (perception of the future as fixed or flexible), and volition (a group moves toward the future or the future moves toward the group). This article is also an experiment in understanding how language can provide insight into the dynamics of prefiguration. I used a 'projective grammars' framework for qualitative analysis of in-depth interviews, ethnographic fieldnotes, newspaper articles, activist produced media (flyers, blog posts, zines, etc.), websites, and ephemera. I suggest that this analytic tool may help social movement scholars investigate projectivity and prefiguration more thoroughly.